2018
DOI: 10.1016/j.ebiom.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Promotes the Degradation of Components of the Type 1 IFN JAK/STAT Pathway and Blocks Anti-viral ISG Induction

Abstract: Anti-retroviral therapy successfully suppresses HIV-1 infection, but fails to provide a cure. During infection Type 1 IFNs normally play an essential role in viral clearance, but in vivo IFN-α only has a modest impact on HIV-1 infection, suggesting its possible targeting by HIV. Here, we report that the HIV protein, Vif, inhibits effective IFN-α signalling via degradation of essential JAK/STAT pathway components. We found that STAT1 and STAT3 are specifically reduced in HEK293T cells expressing Vif and that fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 71 publications
1
27
0
1
Order By: Relevance
“…The innate immune system recognizes invasive viruses through pattern recognition receptors (PRRs) and then activates downstream pathways to produce IFNs; the IFNs then bind to corresponding receptors to activate the JAK-STAT signaling pathway, ultimately inducing antiviral responses to produce the antiviral proteins MX1, OASL, and others (31). Therefore, we wanted to further explore whether SOCS3 affected the expression of downstream antiviral proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The innate immune system recognizes invasive viruses through pattern recognition receptors (PRRs) and then activates downstream pathways to produce IFNs; the IFNs then bind to corresponding receptors to activate the JAK-STAT signaling pathway, ultimately inducing antiviral responses to produce the antiviral proteins MX1, OASL, and others (31). Therefore, we wanted to further explore whether SOCS3 affected the expression of downstream antiviral proteins.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of viruses disrupt the IFNα signaling pathway by degrading the major components of the JAK-STAT signaling pathway. For example, the HIV Vif protein achieves immune evasion by disrupting the IFNα-mediated phosphorylation of STAT1 and STAT3 and reducing the expression of ISG15 (31). However, enterovirus 71 (EV71) inhibits the intracellular type I IFN signaling pathway by downregulating the expression of the JAK1 protein (40).…”
Section: Discussionmentioning
confidence: 99%
“…The protein Vif of HIV has been proposed to play a role in its own catalysis, in the ubiquitination and proteasomal degradation of STAT1 and STAT3 proteins of the JAK/STAT pathway, and in the degradation of monocytic cell lines, which allows HIV-1 to block the antiviral effects of IFN-I. More specifically, Vif-mediated STAT1 and STAT3 inhibition reduces IFN- α induction of ISG-15 [14]. On the other hand, another work has shown that Vpu and Nef are able to block the phosphorylation of Nef without the degradation of STAT1 in T-cell lines [15].…”
Section: Hiv Disrupts Ifn Induction During Treatmentmentioning
confidence: 99%
“…The interaction of IFNs with their receptors on the cell membrane initiates the Janus protein tyrosine kinase/signal transducers and activators of transcription (JAK/STAT) signaling cascade to regulate transcription of IFN-stimulated genes (ISGs) that generate an antiviral state within the cell. IFN-activated JAK/STAT signaling can also create an antiviral state in adjacent cells (Chen et al, 2018;Gargan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%